Analysis of National Lists of Essential Medicines in Ukraine and the Who Model List of Essential Medicines in the Dynamics of the Year - Hanna Panfilova (Journal of Global Pharma Technology, 2019)
The article contains results of dynamic of changes of National lists of Essential medicines in Ukraine during 2001-2017 and the WHO Model list of essential medicines (1977-2017). During a long period of time the WHO International concept of model list of essential medicines was considered to have a complicated dynamic of changes of medicines. In 1977 as compared to 2017, the number of medicines increased twice. Maximum increase (455 drugs) was observed in 2011 and minimum (204 drugs) – as in 1977. The fluctuation of chain increase of the number of medicines, which were included in the WHO Model list of essential medicines from –8,0% (2013) to +22,0% (1979). In the last edition (2017) the WHO Model list of essential medicines was changed significantly, which meet up-to-date requirements of practical medicines development, and the requirements of the society as to the efficiency of medical and pharmaceutical aid. A significant fluctuations of qualitative indicators of the WHO National list of Essential medicines in Ukraine (from 215 to 780 drugs) allow us to state about the absence of a systematic approach and a relevant policy to the implementation of the WHO International concept of Essential medicines in our country to practical health protection and pharmacy. Thus, in 2008 the number of medicines included in the WHO National list of Essential medicines had 780 names, which exceeded the number of medicines of existing edition of the WHO 15th Model list of essential medicines by 1,8. We proved that the last edition (2017) of the National list of Essential medicines, which was confirmed in Ukraine based on the government program “Available medicines”, meets international requirements.Keywords: National Drug Policy, National list of Essential Medicines of Ukraine, Model list of Еessential medicines, рarmaceutical market of Ukraine, Ukraine, World Health Organization.